Total Suspended Solids Dynamics in Tin Mining Exploitation Areas in Northeastern Coastal Waters of Bangka Island: A Remote Sensing Approach - Filialdi Nur Hidayat; Taryono Taryono; Fery Kurniawan (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2026)
The dynamics of total Suspended Solids (TSS) are a characteristic of water quality that can be observed over time, especially in areas where water is used for extractive purposes, such as tin mining areas in Northeastern Coastal Waters of Bangka Island. This study describes the TSS dynamics that occurred in those areas which are covered by Landsat 8 Imagery (Path123/Row 061). This is interesting because the research location is a tin mining site whose exploitation activities have an impact on Total Suspended Solids in the surrounding area. The method used in this study was multispectral analysis of satellite imagery. The algorithm used was developed by Laili et al. (2015). The results show that during the 10-year study period, the dynamics of Total Suspended Solids on the Northeastern Coast of Bangka Island from 2015 to 2024 did not experience significant changes. The annual average values of Total Suspended Solids ranged from 18.48 mg/L to 18.74 mg/L. However, there is a significant difference (p-value of 0.00 on T-Test) between Total Suspended Solids levels within the tin mining area (19.15 mg/L) and those outside the tin mining area (18.64 mg/L).